BERBAGI PENGETAHUAN DENGAN KELOMPOK PEMUDA TANJUNG DAPURA DALAM MEWASPADAI TURBULENSI POLITIK : Sharing Knowledge With Tanjung Dapura Youth Group In Aware Of Political Turbulence - Emanuel Omedetho Jermias; Abdul Rahman; Nurlela; Mubarak Dahlan (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia, which has chosen the path of becoming a democratic country, should no longer question differences in choices in general elections. However, in the course of history, general elections, especially in 2014 and 2019, were marked by divisions in society. This has also become a concern for some groups that a similar incident will occur so that there will be political turbulence in society. On that basis, this service activity is carried out by making youth partners, so that youth can respond wisely to various events related to the 2024 election. This activity is carried out on Jalan Tanjung Dapura by holding discussions with partner groups. The results of the dedication show that young people with the status of first-time voters are very enthusiastic about this activity. They will also participate actively in the 2024 elections democratically. They hope that the elections can take place peacefully, there will be no divisions in society for the sake of the integrity of the nation and state.